Protesta social y poesía. Brasil 2013-2018:Onde no mundo. Onde estão as bombas. - Susana Scramim (Caravelle)
The search for the place from which the poem in mother tongue can be pronounced, blends with the search for the country not yet found. Poems by several authors between 2013 and 2019 protest against this absence. This paper raises questions about this place and the language traits observed during its poetical enunciation. Through their writings, poets propose a historical experience of revolt. I shall examine Vinagre: uma antología de poetas neobarrocos (2013), poems by Lu Menezes (2016) and Tatiana Pequeno (2019), texts that have managed to give an answer through their own poetical language to the street’s social protest shoutings.